Metacognition Knowledge of High School Students in Solving Limit of Functions Problems Viewed from Mathematical Ability - Pathuddin Pathuddin; Intan Purnama Marzuki; Anggraini Anggraini; Bakri Mallo; Sukayasa Sukayasa (Universitas Syiah Kuala, 2023)
The involvement of metacognition in the problem-solving process is paramount. This study aims to obtain a description of the metacognition knowledge of high school students in solving limit of functions problems. This type of research is qualitative descriptive research. The subjects of this study were two students who had high and low mathematical abilities. Data from the results of written assignments and in-depth interviews. The results showed that students with high mathematical abilities in solving limit of functions problems involved the metacognition knowledge they had at each stage of Polya, starting from their declarative, procedural, and conditional knowledge. The subjects with low mathematics at the stage of understanding the problem involved only their declarative knowledge. The step of making a plan involves the declarative knowledge their memory and their procedural knowledge, although incomplete in compiling the ideas. The step of carrying out the plan involves all three knowledge of metacognition that he possesses, while the stage of re- examining involves only his declarative knowledge and his conditional. The results of this research can be a reference in designing limits learning in high school.